(untitled) - Wiger, Donald E. (Hoboken, N.J., 2007)
Designed for practices or clinics of any size and at any stage of development—from start-up through mature business—this easy-to-follow book looks at all the issues involved with starting and running a mental health practice and offers: Practical advice on how to increase business, develop your professional reputation, and set priorities, as well as helpful insights on customer service, employee relations, time management, and coping with stress; Indispensable tools for developing business and management skills to ensure smooth operation and maximum profitability; Useful tips for handling problems encountered by clinic directors and clinic decision-makers; Numerous sample forms and procedural documents
Keywords: Medicine; Practice